PELATIHAN HOSPITALITY SERVICE EXCELLENCE DAN FOOD & BEVERAGE SERVICE PADA USAHA DWE DESA ADAT BATUR KINTAMANI - Ni Luh Putu Intan Nirmalasari; A.A.Ayu Arun Suwi Arianty; Luh Eka Susanti (Fakultas Teknik dan Informatika Universitas PGRI Mahadewa Indonesia, 2026)
Tourism development in Kintamani has increased the need for professional hospitality services, particularly in community-based businesses managed by local human resources. Usaha Dwe Desa Adat Batur Lila Cita Sari Mekar Batur, located at Warung Seked Kintamani, has strong potential to support guest experiences through accommodation and food and beverage services. However, the staff still faced several challenges related to service flow, communication, cleanliness, product consistency, restaurant service techniques, and beverage preparation. This community service activity aimed to improve staff competence through Hospitality Service Excellence and Food and Beverage Service training. The method consisted of initial observation, preparation of training materials, training and mentoring, evaluation, and formulation of recommendations. The training was conducted through material delivery, demonstration, direct practice, service simulation, interactive discussion, restaurant service practice, and bar practice for developing beverage recipes needed by the business. The results showed improvement in staff understanding, confidence, and practical skills in providing cleaner, more responsive, professional, and guest-oriented service. The activity also helped staff recognize the importance of coordination between kitchen, service, and bar operations. In conclusion, practical training based on partner needs can strengthen local staff competence and support better guest experiences at Warung Seked Kintamani.